Economic Transmission Augmentation With Explicit Modeling of the Competition Benefit - Hesamzadeh, M.; Biggar, D.; Hosseinzadeh, N.; Wolfs, Peter (IEEE, 2010)
This paper derives and evaluates a mathematical structure for identifying economically-efficient transmission augmentations. The mathematical structure is based on the concepts of sequential-move and simultaneous-move games in applied mathematics. The Nash equilibrium solution concept has been reformulated as an optimization problem in the proposed structure. The problem of multiple Nash equilibria is managed by introducing the concept of the worst-case Nash equilibrium. Both the economic concepts of the "efficiency benefit" and "competition benefit" of the transmission capacity are explicitly modeled in the proposed structure. A simple three-bus example system and Garver's example system are employed and modified to suit the purpose of analysis. A thorough economic study of these example systems is presented to highlight the concept and operation of the proposed mathematical structure from different perspectives. The results demonstrate the utility of the proposed structure for measuring the total economic efficiency benefit of additional transmission capacity.